The Relationship Between Learning Methods, Participation Of Nurse Educator, And The Student’s Clinical Performance As Perceived By S1 Nursing Students (Stage 1) - Elly Nurachmah; Yulia Yulia (Fakultas Ilmu Keperawatan Universitas Indonesia, 2003)
Abstrak:Pengalaman di klinik memperlihatkan bahwa beberapa rumah sakit mempekerjakan perawat dari lulusan perguruan tinggi. Alasain keaadaan ini adanya persepsi dari manajemen rumah sakit- menolak perawat yang baru lulus. Mereka menganggap bahwa perawat ini tidak siap untuk bekerja karena gagal menunjukkan kemampuan klinik yang diharapkan, yang mungkin disebabkan oleh beberapa faktor. Fenomena di atas menghasilkan asas teoritis yang dapat diperdebatkan karena belum ada temuan ataupun studi yang dapat menjelaskan penyebabnya. Tujuan dari penelitian ini adalah untuk mengidentifikasi hubungan antara metoda pembelajaran di kelas dan laboratorium, partisipasi pembimbing klinik, dengan kinerja klinik yang dipersepsikan oleh mahasiswa program ners yang sedang menjalani tahap profesi. Penelitian ini terdiri dari dua tahap. Disain dari penelitian tahap pertama adalah deskripsi dan analisa korelasi. Data dikumpulkan dengan menggunakan pendekatan cross sectional. Responden yang berpartisipasi sejumlah 120 orang. Metoda pengumpulan data yang digunakan adalah kuesioner terstruktur. Variabel utama yang diuraikan pada penelitian ini adalah metoda pembelajaran, partisipasi pembimbing klinik, dan kinerja klinik mahasiswa. Temuan dari penelitian ini menggambarkan penelitian tahap pertama. Temuan menunjukkan lebih dari separuh responden adalah usia produktif (73.4%), suku Jawa (57.5%), wanita (62.5%), program B (55.8 %), dan memiliki ijazah sekolah menengah umurn (77.5%). Tes kaikuadrat digunakan, dan menunjukkan hubungan yang spesifik antara jenis program, status perkawinan dengan kinerja klinik yang ditampilkan (p=0.00, dan 0,01). Tes regresi logistik digunakan untuk mengidentifikasi variabel yang paling mempengaruhi. Hasilnya menunjukkan bahwa metoda pembelajaran di kelas (p=0.03), jenis program (0.00), status perkawinan (0.01), dan partisipasi pembimbing kinik (0.04) adalah variabel yang paling mempengaruhi kinerja klinik. Peneliti merekomendasikan lahan praktek untuk menyediakan lingkungan pembelajaran yang lebih kondusif dengan meningkatkan fasilitas dan sistem yang dapat digunakan oleh mahasiswa. Untuk institusi pendidikan, harus ada perbaikan yang signifikan dalam menyediakan sistem pembelajaran klinik untuk mahasiswa misalnya dengan meningkatkan kompetensi pembimbing kinik dan mengimplementasikan program preceptorship.Â Abstrack:Clinical experience showed that many hospitals refused to employ nurses with higher degree. The reason behind the situation was the hospital management perception on the performance of the newly hired nurses. They perceived that these nurses were not ready to work due to failure to demonstrate clinical expectancy, which was suspected to have many causal factors. The phenomenon above created a debatable theoretical foundation since there was no study findings supported the reasons. The purpose of the study was to identify the relationship between learning methods in the class and laboratory, the participation of the clinical nurse educator in their clinical learning process, and the studentâ€™s clinical performance as perceived by the students in their professional stage. The study consists of two stages. The design of this first stage study was a descriptive, correlation analysis. The data collected with a cross sectional approach. The study took place in several hospitals in Jakarta and community settings where the students of one faculty of nursing from public university were doing their clinical practice. Sample of the study were students in their final year and were self- involving in the professional first stage. The number of respondent was 120 subjects. Data collection method used in the study was structured questionnaires. Main research variables explored in the study were learning methods, participation of the clinical nurse educator; and clinical performance of the students. The findings in this study were reflecting the first stage. The findings demonstrated that more than half subjects were in the productive age (73.4%), Javanese (57.5%), female (62.5%), from B program (55.8%), and had completed their 12 years general education (77.5%). The chi-square tests were conducted, and showed significant relationships between the type of the program, the marital status and the perceived clinical performance (p=0.00, and 0.01 respectively). A logistic regression test was conducted to identify the most influencing variables. The result demonstrated that learning method in the class (p=0.03), type of the program (0.00), marital status (0.01), and participation of the nurse educator (0.04) were the most influencing variables to the clinical performance. Recommendations were extended to the management of field practice areas to provide more conducive learning environment by improving the facilities and the systems that could be used by the students. To education institution, there should be a significant improvement in providing a clinical teaching system for the students such as improving the competence of nurse educators, and implementing a preceptor ship program